An adaptive congestion control scheme for real-time packet video transport. - Kanakia, Hemant (Computer communication review.)
In this paper we show that modulating the source rate of a video encoder based on feedback information from the network results in graceful degradation in picture quality during periods of congestion. Such source rate modulation techniques have been used in the past in designing video encoders used to generate data at a fixed rate. In such constant bit rate encoders, the source rate modulation is done using feedback information about the occupancy of a local buffer. Since the buffer is local, the feedback information is available instantaneously to the encoder. In the proposed scheme, the feedback information is delayed because it comes from within a packet-switching network. The feedback provides information about the traffic at switches along the path of the video connection. We show that the proposed scheme performs well, even though the information is delayed for relatively large intervals of time. We believe that the use of such schemes will simplify the architecture used for supporting real-time services in future nationwide gigabit networks.